2008
DOI: 10.1016/j.jsat.2008.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Using a standardized patient walk-through to improve implementation of clinical trials

Abstract: This report describes a standardized patient (SP) walk-through to facilitate implementation of a clinical trial within the National Drug Abuse Treatment Clinical Trials Network (CTN). SPs are actors trained to portray a set of symptoms consistently across interactions with multiple clinicians. The Oregon/Hawaii Node of the CTN employed one SP to pilot participant screening processes in a study testing a combined pharmacological and behavioral therapy for women and men dependent on prescription opioid analgesic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…The literature supports the use of SPs to train and assess clinicians [1,5]. Our study supervisors found the use of SPs to be effective in assessing counselor readiness to work with real patients, and the counselors reported that they found the SP exercises to be realistic and helpful for their training.…”
Section: Discussionsupporting
confidence: 67%
“…The literature supports the use of SPs to train and assess clinicians [1,5]. Our study supervisors found the use of SPs to be effective in assessing counselor readiness to work with real patients, and the counselors reported that they found the SP exercises to be realistic and helpful for their training.…”
Section: Discussionsupporting
confidence: 67%
“…Our work extends a prior analysis based on a single standardized patient at one site for one clinical trial (20). The analysis highlights the use of standardized patient walkthroughs to capture issues with study procedures previously unidentified with didactic training alone.…”
Section: Discussionmentioning
confidence: 89%
“…Even more novel are applications of the methodology to enhance training and identify potential for improvement in protocol procedures in clinical trials of interventions for substance use disorders (20). This report identifies cross-study and cross-site common concerns in protocol implementation and recommendations for resolutions to those concerns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adapted from computerized clinical guideline development (Horsky et al 2003), business and management (Gustafson 2004), and medical training (Carney et al 1999), walk-throughs have been used in behavioral health to identify areas for improvement in admission procedures (Ford et al 2007) and to pilot screening processes for a clinical study (Fussell et al 2008). Fussell et al (2008) incorporated the use of a standardized patient, often used in diagnostic studies to assess provider sensitivity to specific presented symptoms (Carney et al 1999), to standardize the walk-through procedure.…”
Section: Introductionmentioning
confidence: 99%